ANALISIS PERKEMBANGAN PRAGMATIK ANAK USIA 3 - 4 TAHUN - Natasya, Zahra Firman; Sit, Masganti (AL-QALAM: JURNAL KEPENDIDIKAN, 2024)
The development of pragmatics in children aged 3-4 years is an important stage in the formation of their complex communication abilities. Pragmatics is a branch of linguistics that focuses on understanding the complex relationship between language and the context of its use. This research aims to better understand the process of pragmatic development in children aged 3-4 years and identify effective strategies in supporting their language and communication development. This is done through analysis of the results of direct observations and interviews with parents or caregivers of children. This research uses a qualitative approach which involves collecting data through direct observation and interviews with parents or caregivers of children. The data obtained was then analyzed inductively to identify relevant patterns and themes in the pragmatic development of children aged 3-4 years. The research results show that children aged 3-4 years have shown significant progress in the development of their communication skills. They have demonstrated a better understanding of the purpose of communication, are able to use language effectively in a variety of contexts, and are beginning to understand the role of non-verbal language in communication. In addition, children have also developed better speaking skills, are able to listen attentively, and use language strategically to influence the environment around them.